Estimation of the Reliability Function of Basic Gompertz Distribution under Different Priors - Awad, Manahel Kh.; Rasheed, Huda A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
In this paper, some estimators for the reliability function R(t) of Basic Gompertz (BG) distribution have been obtained, such as Maximum likelihood estimator, and Bayesian estimators under General Entropy loss function by assuming non-informative prior by using Jefferys prior and informative prior represented by Gamma and inverted Levy priors. Monte-Carlo simulation is conducted to compare the performance of all estimates of the R(t), based on integrated mean squared.